Knowledge KNOWLEDGE WORKER PRODUCTIVITY DI PT TRIKAYARASA JAYA FOOD: PERAN KNOWLEDGE MANAGEMENT MELALUI KEMAMPUAN ADAPTASI DAN KEPUASAN KERJA KARYAWAN - Fernanda, Sherly Amalia; Larassaty, Ayu Lucy (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This research aims to provide an overview of the relevance of knowledge management to knowledge worker productivity which is also mediated by employee adaptability and job satisfaction. This research uses a quantitative approach with PT Trikayarasa Jaya Food Sidoarjo as the object. The research data collection technique uses purposive sampling. And using 70 PT Trikayarasa Jaya Food employees as samples. The data obtained came from filling out a questionnaire which was processed with SmartPLS 4.0. From the results of this research it can be concluded that knowledge management has an effect on knowledge worker productivity, knowledge management has an effect on adaptability, adaptability has an effect on knowledge worker productivity, knowledge management has an effect on job satisfaction, job satisfaction has no effect on knowledge worker productivity, adaptability and satisfaction work has a full mediating role in the influence of knowledge management on knowledge worker productivity.